(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background : Anthropometry is the study of human morphology. Physical variation between the people of different ethnic groups can be recorded by anthropometry. This study was done to establish the anthropometric difference by measuring the nasal parameters among Bengali and Chakma School Going Children. The data of nasal parameters provide important information in plastic surgery, aesthetics and, nationality study and medical jurisprudence. Methods : It was an observational and cross sectional study, convenient sampling was done to select the 50 Bengali and 50 Chakma School Going Children, age ranging from 5-16 yrs old. Data were collected by using standard anthropometric methods with a sliding caliper. Values were expressed as mean ± Standard Deviation (SD).Student T test was used to compare the results. Results : In both sex, among the two ethnic groups, the mean total length and protrusion of nose in the Bengali group was significantly (<0.001) higher than the Chakma ethnicity (48.46±6.75 vs 41.34±4.17, 16.77±2.85 vs 14.48 ±2.22). The mean anatomic width of the nose was higher in Chakma ethnic group. The mean nasal index in the Bengali ethnic group was 67.60 and in the Chakma was 83.38 which shows that the mean nasal index of most Bengali (68%) falls within the Leptorrhine (Narrow nose) type and the most Chakma ethnicity (54%) in the mesorrhine (Broad nose) type. Conclusion : This result represent that the nasal parameters and index play an important role in the ethnicity difference. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 33-36